Camellia sinensis in Dentistry: Technological Prospection and Scientific Evidence. (31st August 2021) - Valadas, Lídia Audrey Rocha; Oliveira Filho, Rosueti Diógenes de; Rodrigues Neto, Edilson Martins; Bandeira, Mary Anne Medeiros; Fonteles, Marta Maria de França; Passos, Vanara Florêncio; Fiallos, Ana Cristina de Mello; Lotif, Mara Assef Leitao; Sena, Nara Juliana Custodio de; Dantas, Thereza Cristina Farias Botelho; Lima Soares, Igor; Lobo, Patricia Leal Dantas; et al.
Abstract : Purpose . This study aimed to evaluate reports of patents for oral care formulations, based on Camellia sinensis ( C. sinensis ), deposited and granted in intellectual property banks. Methods . A survey was conducted through collection, treatment, and analysis of extracted information from patent reports selected. The documentary research was conducted in January 2021 on formulations with C. sinensis for dental applications, including since the first patent deposits until the current time. The risk of bias of clinical trials with these formulations was analyzed to verify the scientific evidence. The data extracted represent the distribution of the number of patents by banks, annual evolution of patent deposits, applicant of patents by country, distribution of patents according to International Patent Classification codes, and the types of patented products. Results . Data and information from 20 selected patents were extracted. The United States Patent and Trademark Office (USPTO) and World Intellectual Property Organization (WIPO) were the banks with the largest number of patents for products/formulations with C. sinensis for oral care applications with 7 (35%) and 6 (30%) patent registrations, respectively. Other banks did not provide patents related to the search. Patents of compositions were the largest with 14 filings, and the remainder of formulations are represented specially by mouthwashes and toothpastes. As for clinical application, 18 patents were filed as products with antimicrobial and antibiofilm action, while 2 patents are directed to the treatment of xerostomia. In general, the aspects of the studies of clinical efficacy pointed to a low risk of bias. Conclusion . The study pointed out a small number of products protected by patents for Camellia sinensis for oral care indication, highlighting mainly mouthwash compositions and formulations. In the methodological parameters of clinical trials carried out with the formulations, the majority pointed out a low risk of bias.